Analysis Of The Effect Of Inftrastructure And Polulation On The Economy Of Java Island - Septriani Septriani (Program Studi Ekonomi Islam Fakultas Ekonomi Universitas Nahdlatul UlamaNusa Tenggara Barat, 2024)
This study aims to analyze the influence of road infrastructure, electricity infrastructure and population on provincial GRDP in Java. The type of data used in this study is secondary data from the Ministry of Finance and the Statistics Center Agency during the 2016-2021 time period. The method used in this study is panel data regression. Based on the regression result, the best model was obtained, namely the Random Effect Model. Furthermore, the results of this study show that partially the variables of road infrastructure, as well as electricity infrastructure have a positive and significant effect on the Provincial GRDP in Java Island at α=5%, while simultaneously the variables of roads infrastructure, electricity infrastructure, and population have a positive and significant effect on GRDP at α=5%. As for the results of the coefficient of determination (R2) test, the Adjusted R-Square value is 0.8414. This result shows that the variables of road infrastructure, electricity infrastructure and population can explain GDP by 84.14 percent while 15.86 percent is explained by other variables outside the model